Situation Report: Bulgaria, 1 September 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Toward Genuine Economic Reform or Mock Perestroika? Intellectuals Stand Up for Ethnic Turks Discussion Club Criticizes the Government for Creating a National Crisis / by Stephen Ashley Unrest among Bulgaria's Pomak Community / by Stephen Ashley A Political Trial in Varna / by Stephen Ashley Two-Year-Old Decision on State Ceremonies Partly Abandoned / by Rada Nikolaev